An analysis of solid-state recycling of aluminium alloy AA6061 from controllable hot extrusion processes - Shamsudin, Shazarel (2018)
Solid-state recycling of machining chip wastes via hot extrusion has nowadays been seen important to reduce energy consumption and greenhouse effect, perceived more important than the recycling by remelting. Characteristics of machining chips that are micro in size and large area-to-volume ratio in nature, melting can cause a massive molten metal vaporization leading to huge material losses. The hot extrusion process has long been recognised as the most outstanding direct recycling method which can result in much better material recovery. However, the high quality weld bonds among chips must be well developed during the process to ensure the mechanical performance of the recycled product is comparable to as-cast material. The optimum weld bond quality often relies on the selection of accurate process parameters to be combined with the appropriate die design. Nevertheless, the use of conventional approach of trial and error to complete the process parameter selection offers an unrealistic implementation, time consuming, and a costly process cycle. This conventional method was identified as the key shortcoming of the current solid-state recycling process. This research provides an investigation into the optimum homogenisation condition for chip-based billet, a mathematical model development which allows the prediction of weld strength recycled materials and a proposed heat treatment for performance improvement. For homogenisation aspect, a series of hot extrusion experiments were performed at different settings of temperature (400 °C - 550 °C) and preheating time (1 - 6 hours). Each extrudate profile was then tested for its tensile strength performance. To further investigate the effect of temperature in homogenisation via damage evolution within the extrudate structure, a numerical simulation using a finite element method was implemented. The normalized Cockcroft and Latham (C & L) fracture criterion was applied. Besides, a mathematical model for tensile bond strength prediction was developed using both theories of thin film bonding and diffusion. All related deformation variables for model calculation were numerically obtained via the finite element simulations, undertaken by the DEFORM 3D software. The model’s validation was done by a series of tensile tests on gear and rectangular profiles, where the predicted strengths were compared with the strengths obtained experimentally. Finally, the heat treatment process was carried out at T6 condition for all samples. For chip-based billet homogenisation, both experimental and numerical findings showed that the billet temperature must be kept higher than 400°C while for preheating time, minimum two hours was required to obtain a satisfactory tensile strength under the extrusion ratio of 11.22 or lower. The derived weld strength model was fairly accurate in predicting the tensile bond strength of extrudate. The average error resulting from the gear profile was 12 % while 23 % was calculated for the rectangular profile, both compared between the predicted and experimental results. The sources of error in the analysis were mainly contributed by the extreme state of strain-rate and deviations in the shear area estimation. The research shows that a great amount of heat or induced normal stress or shear stress was demanded to reduce the threshold strain of weld creation, thus promoting a sound weld bond. The greater magnitude of the normal stress (perpendicular to the extrudate surface) than the yield strength of material increases the real contact area of chips to result in a better cohesion and a delay in the contact time between die and billet enhances diffusion. Finally, the heat treated AA6061-T4 aluminium chips at T6 condition resulted in 105.66 HV, inferior just by ≈ 5 % hardness of as-received AA6061-T6, indicates that the mechanical properties of the direct recycled material can be successfully enhanced for practical applications.